2002
DOI: 10.1128/jcm.40.4.1541-1545.2002
|View full text |Cite
|
Sign up to set email alerts
|

Use of Phylogenetic Analysis of Hepatitis C Virus (HCV) Hypervariable Region 1 Sequences To Trace an Outbreak of HCV in an Autodialysis Unit

Abstract: Hemodialysis patients are at high risk of infection by hepatitis C virus (HCV). The aim of this study was to investigate an HCV outbreak that occurred in an autodialysis unit by using epidemiological and molecular methods. Seroconversion to HCV antibody (anti-HCV) was observed in two patients over an 18-month period; two other patients had previously been recorded as anti-HCV positive. All four patients involved in the outbreak were tested for HCV RNA, and hepatitis C genotype determination was accomplished by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 21 publications
1
20
0
Order By: Relevance
“…Nosocomial transmission of HCV infection has become the main source of infection in chronic hemodialysis patients rather than transmission by blood-derived products. Molecular phylogenetic analyses have shown that many outbreaks of HCV infection are not linked to the transfusion of packed red blood cells or blood products [Allander et al, 1994;Stuyver et al, 1996;Le Pogam et al, 1998;Izopet et al, 1999;Katsoulidou et al, 1999;Grethe et al, 2000;Halfon et al, 2002;Kokubo et al, 2002].…”
Section: Introductionmentioning
confidence: 97%
“…Nosocomial transmission of HCV infection has become the main source of infection in chronic hemodialysis patients rather than transmission by blood-derived products. Molecular phylogenetic analyses have shown that many outbreaks of HCV infection are not linked to the transfusion of packed red blood cells or blood products [Allander et al, 1994;Stuyver et al, 1996;Le Pogam et al, 1998;Izopet et al, 1999;Katsoulidou et al, 1999;Grethe et al, 2000;Halfon et al, 2002;Kokubo et al, 2002].…”
Section: Introductionmentioning
confidence: 97%
“…Several recent studies [31, 52, 54, 59, 65, 79,143,144,145,146,147,148,149,150] and one large study [44] reported nosocomial patient-to-patient transmission of HCV infection among HD patients performing phylogenetic analysis of HCV viral isolates. Although the potential sources of nosocomial transmission could be dialyzer reuse, internal contamination of HD monitors, and contaminated hands and articles, the two former mechanisms are almost unlikely [92, 93, 151, 152].…”
Section: Evidence Of Nosocomial Transmission and Preventive Strategiesmentioning
confidence: 99%
“…These isolates appear to represent a new subtype. They should be analyzed in another region of the viral genome, especially in the hyper variable region E1/E2 which, according to many authors, would best reflect the full extent of subtype variations present in the infected individuals (16) or better yet by sequencing the whole genome (24,44).…”
Section: Discussionmentioning
confidence: 99%
“…Several molecular methods have been used for genotype HCV; nucleotide sequencing of a phylogenetically informative region remains the gold standard (5,16).…”
Section: Discussionmentioning
confidence: 99%